Outcomes of malignant ovarian germ-cell tumors treated in chiang mai university hospital over a nine year period - Vithida Neeyalavira (2018)
Malignant ovarian germ cell tumors (MOGCT) are rare neoplasms that most frequently occur in women at a young reproductive age. There have been limited data regarding this disease from Southeast Asian countries. We therefore conducted a retrospective study to analyze the clinical characteristics and the treatment outcomes of MOGCT treated at our institute between January, 2003 and December, 2012. Seventy-six patients were recruited from this period with the mean age of 21.6 years and 11.8% were pre-puberty. The two most common symptoms were pelvic mass and pelvic pain. Two-thirds of the studied patients presented at an early stage. The most common histology was immature teratoma (34.2%) followed by endodermal sinus tumor (28.9%), dysgerminoma (25%), mixed type (10.5%) and choriocarcinoma (1.3%). Over 80% of these patients received fertility sparing surgery and about 70% received adjuvant chemotherapy with the complete response rate at 73.3% and partial response at 11.1%. The most frequent chemotherapy was BEP regimen (bleomycin, etoposide, cisplatin). With the mean follow up time at 56.0 months, 12 patients (15.8%) developed recurrence and only an advanced stage was the independent prognostic factor. The ten year progression free survival (PFS) and overall survival rate of our study were 81.9% and 86.2%, respectively. In conclusion, MOGCT often occurs at a young age. Treatment with fertility sparing operations and adjuvant chemotherapy with a BEP regimen showed a good outcome. An advanced stage is a significant prognostic factor for recurrence.